Antibiotic Prophylaxis in Transarterial Therapy of Hepatocellular Carcinoma: A Meta-Analysis - Jun Wang; Xiao Dong He; You Cheng Zhang (Canadian Journal of Gastroenterology, 2012)
Transarterial therapies, either alone or in conjunction with adjuvant therapies, have been demonstrated to improve survival rates in patients with hepatocellular carcinoma (HCC). Although generally well tolerated and widely used for more than two decades, transarterial procedures have been reported to be associated with several infectious complications when performed in patients with HCC. However, the question of whether antibiotic prophylaxis is necessary for patients undergoing transarterial procedures for HCC remains controversial. Accordingly, this meta-analysis examined clinical trial evidence regarding the effects of prophylactic antibiotic therapy versus no prophylactic treatment with respect to infectious complications in patients undergoing transarterial therapy for HCC.